The Application of MSCs-Derived Extracellular Vesicles in Bone Disorders: Novel Cell-Free Therapeutic Strategy - Liu, Shuyu; Xu, Xia; Liang, Shujing; Chen, Zhihao; Zhang, Yan; Qian, Airong; Hu, Lifang (Frontiers in Cell and Developmental Biology, 2020)
Bone is crucial for supporting the body, protecting other organs, providing minerals, and secreting hormone to regulate other organ’s function. Bone disorders result in pain and disability, seriously affecting human health, decreasing quality of life and increasing high costs to society. With the rapid increase of aging population worldwide, bone disorders have become one major kind of diseases. Therefore, the efficacious therapies for bone disorders become the main concern of the world. Mesenchymal stem cells (MSCs) have been widely explored as a new therapeutic method for numerous diseases. More recent evidences demonstrate that the therapeutic effect of MSCs is mainly mediated by their extracellular vesicles (EV). MSCs-derived extracellular vesicles (MSCs-EV) is indicated as a novel cell-free alternative to cell therapy with MSCs in regenerative medicine. Here, we review the current knowledge of EV and highlight the application studies of MSCs-EV in bone disorders by focusing on osteoarthritis (OA), rheumatoid arthritis (RA), osteoporosis (OP), and bone fracture. Moreover, we discuss the key issues and perspectives of MSCs-EV as a clinical therapeutic strategy for bone diseases.